Glucose metabolism and gene expression in juvenile zebrafish (Danio rerio) challenged with a high carbohydrate diet: effects of an acute glucose stimulus during late embryonic life - Rocha, Filipa (2015)
Knowledge on the role of early nutritional stimuli as triggers of metabolic pathways in fish is extremely scarce. The objective of the present study was to assess the long-term effects of glucose injection in the yolk (early stimulus) on carbohydrate metabolism and gene regulation in zebrafish juveniles challenged with a high-carbohydrate low-protein (HC) diet. Eggs were microinjected at 1 d post-fertilisation (dpf) with either glucose (2 M) or saline solutions. Up to 25 dpf, fish were fed a low-carbohydrate high-protein (LC) control diet, which was followed by a challenge with the HC diet. Survival and growth of 35 dpf juveniles were not affected by injection or the HC diet. Glucose stimulus induced some long-term metabolic changes in the juveniles, as shown by the altered expression of genes involved in glucose metabolism. On glycolysis, the expression levels of hexokinase 1 (HK1) and phosphofructokinase-6 (6PFK) were up-regulated in the visceral and muscle tissues, respectively, of juveniles exposed to the glucose stimulus, indicating a possible improvement in glucose oxidation. On gluconeogenesis, the inhibition of the expression levels of PEPCK in fish injected with glucose suggested lower production of hepatic glucose. Unexpectedly, fructose-1,6-bisphosphatase (FBP) expression was induced and 6PFK expression reduced by glucose stimulus, leaving the possibility of a specific regulation of the FBP-6PFK metabolic cycle. Glucose metabolism in juveniles was estimated using a [C-14]glucose tracer; fish previously exposed to the stimulus showed lower retention of [C-14]glucose in visceral tissue (but not in muscle tissue) and, accordingly, higher glucose catabolism, in comparison with the saline group. Globally, our data suggest that glucose stimulus at embryo stage has the potential to alter particular steps of glucose metabolism in zebrafish juveniles.